Wyrazy z formantem -acja w gwarach polskich na tle historycznojęzykowym - Jerzy Reichan (Ksiegarnia Akademicka Publishing, 2017)
Words with the -acja Formant in Polish Dialects, Against the Background of Historical Linguistic Data Polish dialectal words with the -acja formant can be divided into two groups: 1) words with Latin roots borrowed directly from Latin or through the mediation of West European languages, e.g. administracja < administrować (Lat. administratio < administrare); mobilizacja < mobilizować (French mobilisation < mobiliser, German Mobilisation < mobilisieren; Lat. mobilis); 2) words with Slavic or German roots (in words borrowed from German), e.g. marnacja < marnować (the Slavic root marn); pielęgnacja < pielęgnować (the German word pflegen). The present article describes both groups. A more detailed description of the second group is presented in a separate paper (Reichan 2012).